Efeitos do citrato de sildenafila sobre a neuroproteção na neuropatia óptica, em ratos (Lewis/SsNHsd) com glaucoma agudo - Silva, Germana Alegro da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Protrude more than 80 million people worldwide and a significant number of animals are affected by glaucoma by the end of this decade. The disease perpetrates as unresolved, forcing them to develop more effective therapeutic alternatives. Vision loss results from the death of retinal ganglion cells (RGCs) and their axons, the fibers that make up the optic nerve. Advances in understanding the pathophysiology show that local ischemia and perfusion abnormalities are critical in the pathogenesis of neuropathy conditions. It has been shown that sildenafil drug vasodilator, inhibits phosphodiesterase type 5 (PDE -5) increases the levels of cyclic guanosine monophosphate extends effects of nitric oxide (NO) and increases cell survival in models of ischemic injury. Aimed to evaluate the neuroprotective effect of sildenafil citrate treatment in rats with induced acute ocular hypertension, by histopathological and morphometric examination of the retina and the evaluation of the expression of markers related to RGC survival , using immunohistochemistry (IHC) and TUNEL labeling. The observed histological parameters: cellular , tissue and vascular and morphometric changes were: thickness of the layers of the retina and ganglion cell count , IHC, there was labeling of caspase-9, caspase-3, Bcl-2, NOS-2, PDE-5, and PDE-6. Eyes of 27 rats, adult (Lewis/ SsNHsd) were evaluated after acute unilateral elevation of intraocular pressure (IOP). Composed by five groups , a control group of 3 animals without glaucoma and untreated and four treated groups consisting of 6 animals with induced unilateral acute glaucoma, of which 3 were treated with Sildenafil and 3 with placebo, these groups were separated by days of glaucoma´s induction to euthanasia, and they received districts dose and period of treatment. The induction of glaucoma was made by anterior chamber paracentesis needle attached to a bottle of saline solution 0.9 %, provided the height of 150 cm ...

Projetam-se que mais de 80 milhões de pessoas no mundo e um número significativo de animais serão atingidos pelo glaucoma até o final desta década. A doença perpetra-se como sem solução, obrigando a que se desenvolvam alternativas terapêuticas mais eficazes. A perda de visão decorre da morte de células ganglionares da retina (CGR) e de seus axônios, que compõem as fibras do nervo óptico. Avanços na compreensão da fisiopatologia evidenciam que isquemia local e que anormalidades de perfusão são condições decisivas na patogênese da neuropatia. Mostrou-se que o Sildenafila, fármaco vasodilatador, inibe a fosfodiesterase do tipo 5 (PDE-5), aumenta os níveis de guanosina monofosfato cíclica, prolonga efeitos do óxido nítrico (ON) e aumenta a sobrevida celular em modelos de lesão isquêmica. Objetivou-se avaliar o efeito neuroprotetor do tratamento citrato de sildenafila em ratos com hipertensão ocular aguda induzida, à histopatologia e à morfometria da retina e quanto à avaliação da expressão de marcadores relacionados à sobrevivência das CGR, empregando-se a imunohistoquímica (IHC) e a marcação TUNEL. Os Parâmetros histológicos observados foram: alterações celulares, vasculares e teciduais e os morfométricos foram: espessura das camadas da retina e contagem de células ganglionares. À IHC, observou-se a marcação da caspase-9, da caspase-3, do Bcl-2, da NOS-2, da PDE- 5, e da PDE-6. Foram avaliados olhos de 27 ratos, machos, adultos (Lewis/SsNHsd). Compuseram-se cinco grupos, um grupo controle composto por 3 animais, sem glaucoma e sem tratamento, e quatro grupos tratados compostos, cada um, por 6 animais com glaucoma agudo unilateral induzido, dos quais 3 foram tratados com Sildenafila e 3 tratados com placebo. Esses grupos foram separados conforme dia de indução do glaucoma até a eutanásia, em 1, 13, 14 e 20 dias, e receberam diferentes doses e períodos de tratamento. A indução do glaucoma ...
Keywords: Rato; Olhos - Doenças; Retina; Glaucoma; Celulas; Fármacos; Vasodilatadores; Eye Diseases and defects